Nanoparticle-containing toughened thermoplastic matrix resins

JP7637677B2Active Publication Date: 2025-02-28HEXCEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022523947
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-23
Filing Date
2020-10-20
Publication Date
2025-02-28
Estimated Expiration
2040-10-20

Smart Images

  • Figure 0007637677000022
    Figure 0007637677000022
  • Figure 0007637677000023
    Figure 0007637677000023
  • Figure 0007637677000001
    Figure 0007637677000001
Patent Text Reader

Abstract

A pre-impregnated composite material (prepreg) that can be cured / molded to form an aerospace composite part is disclosed. The prepreg includes carbon reinforcing fibers and an uncured resin matrix. The resin matrix includes an epoxy resin component, polyethersulfone as a toughening agent, a thermoplastic particle component, a nanoparticle component, and a curing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to pre-impregnated composite materials (prepregs) used to fabricate high performance composite parts, particularly suitable for use as aerospace components. The present invention relates to epoxy resins reinforced with thermoplastic materials and used as the resin matrix of such prepregs. More particularly, the present invention relates to such thermoplastic reinforced epoxy resins containing nanoparticles. [Background technology]

[0002] Composite materials are typically composed of two main components: a resin matrix and reinforcing fibers. Composite materials are often required to perform in demanding environments, such as aerospace, where the physical limits and properties of composite parts are critical.

[0003] Pre-impregnated composite materials (prepregs) are widely used in the manufacture of composite parts. Pre-pregs are a combination that typically includes uncured resin and fiber reinforcement in a form ready for molding and curing into a final composite part. Pre-impregnating the fiber reinforcement with resin allows the manufacturer to carefully control the amount and location of resin that is impregnated into the fiber network, ensuring that the resin is distributed in the network as needed. It is well known that the relative amounts of fiber and resin in a composite part, as well as the distribution of resin within the fiber network, affect the structural properties of the part.

[0004] Prepregs are the preferred material for use in the manufacture of load-bearing or primary structural components, particularly aerospace primary structural components such as wings, fuselages, bulkheads, and control surfaces. It is important that these components have sufficient strength, damage tolerance, and other requirements routinely established for such components and structures.

[0005] Fiber reinforcements commonly used in aerospace prepregs are multidirectional woven fabrics or unidirectional tapes containing fibers running parallel to one another. The fibers are typically in the form of bundles of many individual fibers or filaments called "tows." The fibers or tows can also be chopped and randomly oriented in the resin to form nonwoven mats. These various fiber reinforcement structures are combined with carefully controlled amounts of uncured resin. The resulting prepregs are typically placed between protective layers and rolled up for storage or transport to the manufacturing facility. The combination of carbon fiber with an epoxy resin matrix has become a common combination in aerospace prepregs.

[0006] The prepreg may be in the form of short segments of chopped unidirectional tape that are randomly oriented to form a nonwoven mat of chopped unidirectional tape. This type of prepreg is called a "quasi-isotropic chopped" prepreg. Quasi-isotropic chopped prepreg is similar to more traditional nonwoven fiber mat prepregs, except that rather than chopped fibers, short lengths of chopped unidirectional tape (chips) are randomly oriented within the mat. This material is commonly used as a sheet molding compound to form parts and molds for use in making the parts.

[0007] The compressive and tensile strengths of a cured composite part are largely determined by the individual properties of the reinforcing fibers and matrix resin, as well as the interaction between these two components. In addition, the fiber-to-resin volume ratio is an important factor. In many aerospace applications, it is desirable for composite parts to exhibit high compressive and tensile strengths. The open hole compression (OHC) test is the standard measure of the compressive strength of a composite material. The open hole tensile (OHT) test is also the standard measure of the tensile strength of a composite material.

[0008] In many aerospace applications, it is desirable for composite parts to exhibit both high compressive strength and high tensile strength. However, attempts to improve compressive strength can adversely affect other desirable properties, including tensile strength. Thus, it can be difficult to simultaneously increase both the compressive strength and tensile strength of a composite part.

[0009] Selecting a resin with a higher modulus can be an effective way to improve the compressive strength of a composite. However, this can tend to reduce damage tolerance, typically measured by reducing compressive properties such as compression after impact (CAI) strength. Thus, it can be difficult to simultaneously increase both compressive strength and / or tensile strength without adversely affecting damage tolerance.

[0010] Multiple layers of prepregs are commonly used to form composite parts with laminated structures. Delamination in such composite parts is an important failure mode. Delamination occurs when two layers peel away from each other. Important design limit factors include both the energy required to initiate a delamination and the energy required to propagate it. Delamination initiation and propagation are often determined by examining Mode I and Mode II fracture toughness. Fracture toughness is usually measured using composites with unidirectional fiber orientation. Interlaminar fracture toughness of composites is quantified using G1c (Double Cantilever Beam) and G2c (End Notch Flex) tests. In Mode I, the pre-crack laminate failure is dominated by delamination forces, and in Mode II, the crack propagates due to shear forces.

[0011] One approach to improve the interlaminar fracture toughness of parts made from carbon fiber / epoxy resin prepregs has been to introduce thermoplastic sheets as interleaves between the layers of the prepregs. However, this approach tends to result in a stiff, non-adhesive material that is difficult to use. Another approach has been to add thermoplastic particles to the epoxy resin so that a resin interlayer containing the thermoplastic particles is formed between the fiber layers of the final part. Polyamides have been used as such thermoplastic particles. It is also known to include thermoplastic toughening agents in epoxy resins. Toughening agents such as polyethersulfone (PES) or polyetherimide (PEI) are dissolved in the epoxy resin before application to the carbon fibers. Thermoplastic toughened epoxy resins containing a combination of both thermoplastic toughening particles and thermoplastic toughening agents have been used in combination with carbon fibers to make aerospace prepregs.

[0012] The epoxy resin matrix may include one or more types of epoxy resin. It is known that various combinations of different types of epoxy resins can result in significant changes in the properties of the final composite part. The curing agent used to cure the epoxy resin matrix can also substantially affect the properties of the final composite part. When formulating epoxy resins for use as the resin matrix of an aerospace prepreg, it is difficult to predict whether a new combination of epoxy resin type and curing agent will give the desired combination of properties required for the aerospace part. This is especially true when thermoplastic toughening agents and thermoplastic particles form part of the epoxy resin formulation. Thus, many tests are required when formulating a new thermoplastic toughened epoxy resin to determine whether the resin is suitable for use as the resin matrix of an aerospace prepreg.

[0013] While existing aerospace prepregs are suitable for their intended use of providing strong, damage tolerant composite parts, there is still a continuing need to provide aerospace prepregs that can be used to make composite parts that exhibit a desirable combination of high tensile and compressive strength (OHC and OHT), while maintaining high levels of damage tolerance (CAI) and interlaminar fracture toughness (G1c and G2c). Summary of the Invention

[0014] In accordance with the present invention, a pre-impregnated composite material (prepreg) is provided that has high levels of strength and that can be molded to form composite parts having high levels of damage tolerance and interlaminar fracture toughness.

[0015] The pre-impregnated composite material of the present invention is comprised of reinforcing fibers and an uncured resin matrix. The uncured resin matrix includes a resin component comprised of one or more epoxy resins and a hardener. The uncured resin matrix further includes a thermoplastic particle component, a thermoplastic toughening agent, and a nanoparticle component.

[0016] The present invention also includes methods of making the prepregs and methods of forming the prepregs into a wide variety of composite parts. The present invention also includes composite parts made using the improved prepregs.

[0017] It has been found that resins having the matrix resin formulations described above can be used to form prepregs that can be molded to form composite parts having unexpectedly high levels of both compressive and tensile strength.

[0018] The above and many other features and attendant advantages of the present invention will become better understood by reference to the following detailed description when taken in conjunction with the accompanying drawings. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a perspective view of an aircraft illustrating an exemplary primary aircraft structure that may be fabricated using composite materials according to the present invention.

[0020] [Diagram 2] 1 is a partial view of a helicopter rotor blade illustrating an exemplary aircraft primary structure that may be fabricated using composite materials according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The uncured epoxy resin composition according to the present invention can be used in a wide variety of situations where a thermoplastic toughened epoxy resin matrix is ​​desired. The uncured epoxy resin composition can be used alone, but is generally used as a matrix resin in combination with a fiber substrate to form a composite material composed of a fiber substrate and a resin matrix. The composite material can be in the form of a prepreg, a partially cured prepreg, or a fully cured final part. The term "uncured" as used herein in relation to a prepreg; a resin prior to impregnation of a fiber substrate; a resin matrix formed upon impregnation of a fibrous substrate with a resin; or a composite material, covers an item that may be somewhat cured, but is not fully cured to form a final composite part or structure.

[0022] The uncured composite materials may be used for any intended purpose, but are preferably used in making parts for aerospace airframes, such as commercial and military aircraft. For example, the uncured composite materials may be used to make non-primary (secondary) aircraft structures. However, the uncured composite materials are preferably used in structural applications, such as the primary structure of an aircraft. The primary structure or parts of an aircraft are elements of either a fixed-wing or rotorcraft aircraft that are subject to high stresses during flight and are essential for the aircraft to maintain controlled flight. The uncured composite materials may also be used in other structural applications, generally to make load-bearing parts and structures.

[0023] FIG. 1 illustrates a fixed-wing aircraft at 10 including several exemplary aircraft primary structures and components that may be fabricated using uncured composite materials according to the present invention. Exemplary primary components or structures include a wing 12, a fuselage 14, and a tail assembly 16. The wing 12 includes several exemplary aircraft primary components such as an aileron 18, a leading edge 20, a wing slat 22, a spoiler 24, a trailing edge 26, and a trailing edge flap 28. The tail assembly 16 also includes several exemplary primary components such as a rudder 30, a fin 32, a horizontal stabilizer 34, an elevator 36, and a tail section 38. FIG. 2 illustrates the outer end of a helicopter rotor blade 40 including a wing spar 42 and an outer surface 44 as the aircraft primary structure. Other exemplary aircraft primary structures include the wing spars, as well as various flanges, clips, and connectors that connect the primary components together to form the primary structure.

[0024] The pre-impregnated composite material (prepreg) of the present invention can be used to replace existing prepregs used to form composite parts in the aerospace industry and any other applications requiring high structural strength and damage tolerance. The present invention involves replacing the existing resins used to make the prepregs with the resin formulation of the present invention. Thus, the resin formulation of the present invention is suitable for use as a matrix resin in conventional prepreg manufacturing and curing processes.

[0025] The pre-impregnated composite material of the present invention is comprised of reinforcing fibers and an uncured resin matrix. The reinforcing fibers can be of any conventional fiber configuration used in the prepreg and composite sheet molding industries. The reinforcing fibers are preferably carbon fibers.

[0026] The resin used to form the resin matrix (matrix resin) includes a resin component composed of one or more epoxy resins. Exemplary resin components may include difunctional epoxy resins and / or multifunctional epoxy resins as all or part of the epoxy resin component. Difunctional epoxy resins include any suitable epoxy resins having two epoxy functional groups. Difunctional epoxy resins may be saturated, unsaturated, cycloaliphatic, cycloaliphatic, or heterocyclic. Difunctional epoxies may be used alone or in combination with multifunctional epoxy resins to form the resin component. Resin components containing only multifunctional epoxies are also possible.

[0027] By way of example, difunctional epoxy resins include those based on (optionally brominated) bisphenol F, diglycidyl ethers of bisphenol A, glycidyl ethers of phenol-aldehyde adducts, glycidyl ethers of aliphatic diols, diglycidyl ethers, diethylene glycol diglycidyl ether, Epikote, Epon, aromatic epoxy resins, epoxidized olefins, brominated resins, aromatic glycidyl amines, heterocyclic glycidyl imidines and amides, glycidyl ethers, fluorinated epoxy resins, or any combination thereof. The difunctional epoxy resin is preferably selected from diglycidyl ethers of bisphenol F, diglycidyl ethers of bisphenol A, diglycidyl dihydroxynaphthalene, or any combination thereof. Most preferred is the diglycidyl ether of bisphenol F. Diglycidyl ethers of bisphenol F are commercially available from Huntsman Advanced Materials (Salt Lake City, UT) under the trade names Araldite GY281 and GY285, and from Ciba-Geigy (Tarrytown, NY) under the trade name LY9703. Another exemplary difunctional resin is DER 332, available from Dow Chemical Company (Freeport, TX).

[0028] Exemplary multifunctional epoxy resins include trifunctional and / or tetrafunctional epoxy resins. Multifunctional epoxy resins can be saturated, unsaturated, cycloaliphatic, cycloaliphatic, or heterocyclic. Suitable multifunctional epoxy resins include, by way of example, those based on phenol and cresol epoxy novolacs, glycidyl ethers of phenol-aldehyde adducts; glycidyl ethers of dialiphatic diols; diglycidyl ethers; diethylene glycol diglycidyl ethers; aromatic epoxy resins; dialiphatic triglycidyl ethers, aliphatic polyglycidyl ethers; epoxidized olefins; brominated resins; aromatic glycidyl amines; heterocyclic glycidyl imidines and amides; glycidyl ethers; fluorinated epoxy resins, or any combination thereof.

[0029] A trifunctional epoxy resin has three epoxy groups substituted directly or indirectly in the para or meta orientation on a phenyl ring in the backbone of the compound. A tetrafunctional epoxy resin has four epoxy groups substituted directly or indirectly in the meta or para orientation on a phenyl ring in the backbone of the compound.

[0030] The phenyl ring may be further substituted with other suitable non-epoxy substituents. Suitable substituents include, by way of example, hydrogen, hydroxyl, alkyl, alkenyl, alkynyl, alkoxyl, aryl, aryloxyl, aralkyloxyl, aralkyl, halo, nitro, or cyano. Suitable non-epoxy substituents may be attached to the phenyl ring at the para or ortho positions, or at the meta positions not occupied by epoxy groups. Suitable tetrafunctional epoxy resins include N,N,N',N'-tetraglycidyl-m-xylylenediamine (available under the name Tetrad-X from Mitsubishi Gas Chemical Company, Inc., Chiyoda-ku, Tokyo, Japan) and Erisys GA-240 (available from CVC Chemicals, Morristown, New Jersey).

[0031] Suitable trifunctional epoxy resins include, by way of example, those based on phenol and cresol epoxy novolacs, glycidyl ethers of phenol-aldehyde adducts; aromatic epoxy resins; dialiphatic triglycidyl ethers, aliphatic polyglycidyl ethers; epoxidized olefins; brominated resins; aromatic glycidyl amines and glycidyl ethers; heterocyclic glycidyl imidines and amides; glycidyl ethers; fluorinated epoxy resins or any combination thereof.

[0032] A preferred resin used to form the resin matrix (matrix resin) includes a resin component comprised of a hydrocarbon epoxy novolac resin in combination with a trifunctional epoxy resin and optionally a tetrafunctional epoxy resin. The matrix resin further includes a thermoplastic particle component, a thermoplastic toughening agent, a nanoparticle component, and a curing agent.

[0033] The hydrocarbon epoxy novolac resin preferably has a dicyclopentadiene backbone and is commercially available from Huntsman Corporation (The Woodlands, Texas) as TACTIX 556. This type of hydrocarbon novolac resin is referred to herein as dicyclopentadiene novolac epoxy resin. The chemical formula for TACTIX 556 is: [ka]

[0034] TACTIX 556 is an amber to dark semi-solid hydrocarbon epoxy novolac resin with an epoxy index (ISO 3001) of 4.25-4.65 eq / kg and an epoxy equivalent weight (ISO 3001) of 215-235 g / eq. The viscosity (ISO 9371B) of TACTIX 556 at 79°C is 2250 mPa·s. Dicyclopentadiene epoxy novolac resins other than TACTIX 556 may be used in place of TACTIX 556 as long as they have the same chemical formula and properties. For example, another suitable dicyclopentadiene epoxy novolac resin is XD-1000-2L, available from Nippon Kayaku Co., Ltd. (Chiyoda-ku, Tokyo). TACTIX 556 and XD-1000-2L are preferred hydrocarbon epoxy novolac resins for use in accordance with the present invention.

[0035] When a tetrafunctional epoxy resin is included in the preferred resin component, the uncured resin component is comprised of a dicyclopentadiene epoxy novolac resin, a trifunctional epoxy resin, and a tetrafunctional epoxy resin, this embodiment being referred to herein as DEN / TRIF / TETF matrix resin.

[0036] In the DEN / TRIF / TETF matrix resin, a preferred exemplary trifunctional epoxy resin is triglycidyl para-aminophenol. Triglycidyl para-aminophenol is commercially available from Huntsman Advanced Materials (The Woodlands, Texas) under the trade name Araldite MY0510. Another suitable trifunctional epoxy resin is triglycidyl meta-aminophenol. Triglycidyl meta-aminophenol is commercially available from Huntsman Advanced Materials (The Woodlands, Texas) under the trade name Araldite MY0600 and from Sumitomo Chemical Co., Ltd. (Osaka, Japan) under the trade name ELM-120. Other trifunctional epoxy resins may be used, provided they have the same or similar properties as those of triglycidyl para-aminophenol or triglycidyl meta-aminophenol.

[0037] In an embodiment of the DEN / TRIF / TETF matrix resin, an exemplary tetrafunctional epoxy resin is N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane (TGDDM), commercially available from Huntsman Advanced Materials (The Woodlands, Texas) as Araldite MY720 and MY721, or from Sumitomo Chemical Co., Ltd. (Chuo-ku, Tokyo) as ELM 434. Other tetrafunctional epoxy resins may be used, provided they have the same or similar properties as those of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane.

[0038] In another preferred embodiment of the invention, the resin component contains only dicyclopentadiene novolac epoxy resin and triglycidyl aminophenol epoxy resin. In the resin component of this embodiment, referred to herein as DEN / TRIF matrix resin, the dicyclopentadiene novolac epoxy resin is present in the range of 4 wt% to 20 wt%, based on the total weight of the uncured resin matrix. Preferably, the dicyclopentadiene novolac epoxy resin is present in the range of 5 wt% to 15 wt%, based on the total weight of the uncured resin matrix. More preferably, the dicyclopentadiene novolac epoxy resin is present in the range of 6 wt% to 10 wt%, based on the total weight of the uncured resin matrix.

[0039] In DEN / TRIF matrix resins, the triglycidyl aminophenol epoxy resin is present in the range of 20% to 50% by weight based on the total weight of the uncured resin matrix. Preferably, the triglycidyl aminophenol epoxy resin is present in the range of 25% to 45% by weight based on the total weight of the uncured resin matrix. More preferably, the triglycidyl aminophenol epoxy resin is present in the range of 30% to 40% by weight based on the total weight of the uncured resin matrix. Triglycidyl meta-aminophenol is a preferred type of triglycidyl aminophenol epoxy resin for DEN / TRIF matrix resins.

[0040] In the DEN / TRIF matrix resin, the weight ratio of triglycidyl aminophenol epoxy resin to dicyclopentadiene novolac epoxy resin can vary from 2:1 to 8:1. The preferred weight ratio range of triglycidyl aminophenol epoxy resin to dicyclopentadiene novolac epoxy resin is 3:1 to 5:1. Most preferred is a weight ratio of triglycidyl aminophenol epoxy resin to dicyclopentadiene novolac epoxy resin of about 4.3:1.

[0041] The uncured resin matrix according to the present invention also includes a thermoplastic particle component containing one or more types of thermoplastic particles. An exemplary thermoplastic particle is a polyamide particle formed from a polymeric condensation product of bis(4-aminocyclohexyl)methane, including its methyl derivative, and an aliphatic dicarboxylic acid selected from the group consisting of decanedicarboxylic acid and dodecanedicarboxylic acid. Bis(4-aminocyclohexyl)methane and its methyl derivatives are referred to herein as the "amine component". Bis(4-aminocyclohexyl)methane is also known as 4,4'-diaminocyclohexylmethane. This type of polyamide particle and the method of making it are described in detail in U.S. Patent Nos. 3,936,426 and 5,696,202, the contents of which are incorporated herein by reference.

[0042] The formula for the amine component of the polymeric condensation product is: [ka] where R2 is hydrogen and R1 is either methyl or hydrogen.

[0043] In formulas AC-G, when R1 is methyl and R2 is hydrogen, the formula of the resulting monomer unit of the polymeric condensation product can be represented as follows: [ka]

[0044] The molecular number of the polymeric condensation product ranges from 14,000 to 20,000, with a molecular number of about 17,000 being preferred.

[0045] The polyamide particles should have a particle size of less than 100 microns. The particle size is preferably in the range of 5 to 60 microns, more preferably 10 to 30 microns. The average particle size is preferably 15 to 25 microns. The shape of the polyamide particles can be regular or irregular. For example, the particles can be substantially spherical or can be jagged particles.

[0046] One exemplary polyamide particle is made from a polyamide having the above formula (AC-G) in which the amine component of the polymeric condensation product has both R1 and both R2 are hydrogen. Such polyamide particles can be made from a polymeric condensation product of 3,3'-dimethyl-bis(4-aminocyclohexyl)-methane and 1,10-decanedicarboxylic acid. The polyamide particles are made by combining 13,800 grams of 1,10-decanedicarboxylic acid and 12,870 grams of 3,3'-dimethyl-bis(4-aminocyclohexyl)methane with 30 grams of 50% aqueous phosphoric acid, 150 grams of benzoic acid, and 101 grams of water in a heated containment vessel. The mixture is stirred in a pressure autoclave until homogeneous. After compression, decompression, and degassing steps, the polyamide condensation product is extruded as a strand, passed through cold water, and granulated to form polyamide particles. Polyamide particles where both R1 are methyl and both R2 are hydrogen can also be made from GRILAMID TR90, available from EMS-Chime (Sumter, South Carolina), which is a polymeric condensation product of 3,3'-dimethyl-bis(4-aminocyclohexyl)-methane and 1,10-decanedicarboxylic acid.

[0047] Another exemplary polyamide particle is made from a polyamide having the above formula (AC-G) where R1 and R2 are both hydrogen, the amine component of the polymeric condensation product. Such polyamide particles can be made in a similar manner to that described above, except that the polyamide is a polymeric condensation product of bis(4-aminocyclohexyl)-propane and 1,10-decanedicarboxylic acid. The formula of the amine component of this polymeric condensation product is as follows: [ka] Formula AC-I corresponds to the above general formula (AC-G) in which R1 and R2 are hydrogen. Furthermore, the hydrogen groups present at the 2-, 5-, and 6-positions of the cyclohexane group implied in general formula (AC-G) are specifically shown in formula AC-I.

[0048] When the amine component is bis(4-aminocyclohexyl)methane (formula AC-I), the formula of the monomer unit of the polymeric condensation product of AC-I and 1,10-decanedicarboxylic acid is the same as formula I above, except that the methyl group attached to the 3- or meta-position on each cyclohexyl group or ring is replaced with hydrogen as shown in formula II. [ka]

[0049] The molecular number of the polymeric condensation product formed from monomer unit II ranges from 14,000 to 20,000, with a molecular number of about 17,000 being preferred. The polyamide particles formed from this polymeric condensation product should also have a particle size of less than 100 microns. It is also preferred that the particle size ranges from 3 to 60 microns, more preferably from 10 to 30 microns. It is also preferred that the average particle size ranges from 15 to 25 microns. The shape of the polyamide particles can also be regular or irregular. For example, the particles can be substantially spherical or can be jagged particles.

[0050] The monomer units corresponding to formula II can be in the form of stereoisomers in which the nitrogen groups attached to the cyclohexyl ring are in the cis-cis, cis-trans or trans-trans orientation. The polyamides formed from monomer II can contain one, two or all three stereoisomers. Polyamides containing a mixture of all three monomer stereoisomers tend to be amorphous, while polyamides composed primarily of one stereoisomer tend to be semi-crystalline. Processing conditions are controlled to give the desired mixture of stereoisomers. Trogamid® CX9704 is an exemplary amorphous polyamide that is a mixture of all three isomeric forms of formula II. Trogamid® CX9704 is available from Evonik, Mobile, Alabama. Trogamid® CX9705 is an exemplary semi-crystalline polyamide composed primarily of the trans-trans isomeric form of formula II. Trogamid® CX9705 is available from Evonik (Mobile, Alabama).

[0051] The preferred polyamide particles are hybrid polyamide particles, each hybrid polyamide particle containing a mixture of the amorphous and semi-crystalline polyamides described above. The hybrid polyamide particles are made by dissolving the desired amount of amorphous and semi-crystalline polyamides in a suitable solvent, such as ethylene glycol, to form a hybrid mixture. The hybrid mixture is then extruded and / or processed according to conventional polyamide processing procedures to remove the solvent and form the desired hybrid particles, each containing a mixture of amorphous and semi-crystalline polyamides.

[0052] The hybrid polyamide particles should have a particle size of less than 100 microns. The hybrid polyamide particle size is preferably in the range of 3 to 60 microns, more preferably 10 to 30 microns. The average hybrid polyamide particle size is preferably 15 to 25 microns. The shape of the hybrid polyamide particles can also be regular or irregular. For example, the hybrid polyamide particles can be substantially spherical or can be jagged particles.

[0053] The hybrid polyamide particles are made from a hybrid mixture containing amorphous polyamide and semi-crystalline polyamide in amounts such that the resulting hybrid polyamide particles each contain 20-80 wt% amorphous polyamide and 20-80 wt% semi-crystalline polyamide, based on the total weight of the hybrid polyamide particles. Preferably, each hybrid polyamide particle contains 65-75 wt% amorphous polyamide and 25-35 wt% semi-crystalline polyamide, based on the total weight of the hybrid polyamide particles. Most preferred are hybrid polyamide particles containing 70±1 wt% amorphous polyamide and 30±1 wt% semi-crystalline polyamide, based on the total weight of the hybrid polyamide particles.

[0054] In this specification, hybrid polyamide particles are identified by the relative amount of amorphous polyamide and semi-crystalline polyamide present in each hybrid polyamide particle.For example, a hybrid polyamide particle containing a mixture of 70% by weight of CX9704 polyamide (amorphous) and 30% by weight of CX9705 polyamide (semi-crystalline) is identified as hybrid polyamide particle 70A / 30SC, and a hybrid polyamide particle containing a mixture of 30% by weight of CX9704 polyamide (amorphous) and 70% by weight of CX9705 (semi-crystalline) polyamide is identified as hybrid polyamide particle 30A / 70SC.

[0055] Differential scanning calorimetry (DSC) is a standard test used to measure the crystallinity and amorphousness of polymers. Table A shows the DSC test results of an exemplary amorphous polyamide (Trogamid® CX9704), an exemplary semi-crystalline polyamide (Trogamid® CX9705), and an exemplary hybrid polyamide composed of a mixture of Trogamid® CX9704 and Trogamid® CX9705, which were used to make hybrid polyamide particles 70A / 30SC and 30A / 70SC. [Table 1]

[0056] The above description of the polyamide component, including polyamide particles that are hybrid polyamide particles, is not limited to polyamides having monomer units of formula II. Any polyamide that is used to toughen epoxy resins and can be made in amorphous and semi-crystalline forms can be used to form the hybrid polyamide particles.

[0057] The thermoplastic particle component may also include one or more other types of polyamide particles typically used in thermoplastic toughened epoxy resins including, for example, polyamide (PA) 11, PA6, PA12, PA6 / PA12 copolymer, PA4, PA8, PA6.6, PA4.6, PA10.10, PA6.10, and PA10.12.

[0058] A preferred exemplary thermoplastic particle component contains a first group of polyamide particles that do not contain crosslinked polyamide, and a second group of polyamide particles that contain crosslinked polyamide.

[0059] The first group of polyamide particles can be either hybrid polyamide particles as described above, or polyamide particles that do not contain crosslinked polyamide and are typically used in thermoplastic toughened epoxy based prepregs. Such particles can be composed of polyamide (PA) 11, PA6, PA12, PA6 / PA12 copolymer, PA4, PA8, PA6.6, PA4.6, PA10.10, PA6.10 and PA10.12. Non-crosslinked polyamide particles are commercially available from several sources. Suitable non-crosslinked polyamide 12 particles are available from Kobo Products under the trade name SP10L. SP10L particles contain more than 98% by weight PA12. The particle size distribution is between 7 microns and 13 microns, with an average particle size of 10 microns. The density of the particles is 1 g / cm 3 It is preferred that the PA12 particles are at least 95% by weight PA12, excluding the moisture content. It is also preferred that the hybrid polyamide particles are at least 95% by weight amorphous and semi-crystalline polyamide, excluding the moisture content.

[0060] Other suitable non-crosslinked particles can be obtained from Arkema (Colombes, France) under the trade names Orgasol 1002 powder and Orgasol 3803 powder. Orgasol 1002 powder is composed of 100% PA6 particles with an average particle size of 20 microns. Orgasol 3803 is composed of particles that are a copolymer of 80% PA12 and 20% PA6, with an average particle size of 17 to 24 microns. Orgasol 2002 is a powder composed of non-crosslinked PA12 particles that can also be used for the first group of particles.

[0061] The preferred non-crosslinked polyamide particles for the first group of thermoplastic particles are polyamide 11 particles, which are also commercially available from several sources. Polyamide 11 particles are available from Arkema (Colombes, France) under the trade name Rislan PA11. These particles contain more than 98% by weight PA11 and have a particle size distribution between 15 microns and 25 microns. The average particle size is 20 microns. The density of Rislan PA11 particles is 1 g / cm3 The PA11 particles are preferably at least 95% by weight PA11, excluding the water content.

[0062] A second group of thermoplastic polyamide particles are those that contain crosslinked polyamide on the surface of the particle, in the interior of the particle, or both. Crosslinked polyamide particles can be made from polyamide that is crosslinked prior to particle formation, or non-crosslinked polyamide particles may be treated with a suitable crosslinking agent to produce crosslinked polyamide particles.

[0063] Suitable crosslinked particles include crosslinked PA11, PA6, PA12, PA6 / PA12 copolymer, PA4, PA8, PA6.6, PA4.6, PA10.10, PA6.10 and PA10.12. Any of the crosslinkers commonly used to crosslink polyamides are suitable. Examples of crosslinkers are epoxy crosslinkers, isocyanate crosslinkers, carbodiimide crosslinkers, acyllactam crosslinkers and oxazoline crosslinkers. Preferred crosslinked particles are PA12 particles containing PA12 crosslinked with an epoxy crosslinker. Procedures used to crosslink thermoplastic polymers, including polyamides, are known. See, for example, U.S. Pat. No. 6,399,714, U.S. Pat. No. 8,846,818 and U.S. Patent Application Publication No. 2016 / 0152782 A1. The contents of these three references are incorporated herein by reference.

[0064] Crosslinked PA12 particles are commercially available from Arkema (Colombes, France) under the trade name ORGASOL 2009 polyamide powder, also known as CG352. The PA12 particles present in the ORGASOL 2009 polyamide powder are composed of at least 40% PA12 crosslinked with an epoxy-based crosslinker. The ORGASOL 2009 crosslinked polyamide particles have an average particle size of 14.2 microns, with only 0.2% of the particles having a diameter greater than 30 microns. The melting point of the ORGASOL 2009 crosslinked particles is 180° C. The specific surface area of ​​the ORGASOL 2009 particles is 1.9, and the moisture content of the particles is 0.34%.

[0065] The crosslinked polyamide particles should each contain 40-70% crosslinked polyamide, preferably 40-60% crosslinked polyamide.

[0066] Preferably, both the non-crosslinked and crosslinked polyamide particles should have a particle size of less than 100 microns. The particle size is preferably in the range of 5 to 60 microns, more preferably 5 to 30 microns. The average particle size is preferably 5 to 20 microns. The shape of the particles may be regular or irregular. For example, the particles may be substantially spherical or may be jagged shaped particles. The average particle size of the non-crosslinked particles is preferably larger than the average particle size of the crosslinked particles. Preferably, the average particle size of the non-crosslinked particles is in the range of 15 to 25 microns and the average particle size of the crosslinked particles is in the range of 10 to 20 microns.

[0067] The thermoplastic particle component is present in the range of 5% to 25% by weight based on the total weight of the uncured resin matrix. Preferably, 10 to 20% by weight of the thermoplastic particle component is present. When a combination of crosslinked and non-crosslinked particles is used, the relative amounts of non-crosslinked and crosslinked particles can vary. The weight ratio of non-crosslinked to crosslinked particles can range from 4:1 to 1.5:1. Preferably, the weight ratio of non-crosslinked to crosslinked particles ranges from 3.5:1 to 2.5:1. A combination of non-crosslinked polyamide particles and crosslinked particles is a preferred thermoplastic particle component for use in embodiments of the DEN / TRIF matrix resin.

[0068] In embodiments of the DEN / TRIF matrix resin, the total amount of polyamide particles in the uncured resin can vary from 9 to 21% by weight based on the total weight of the uncured resin. Preferably, the total amount of polyamide particles in the uncured resin ranges from 11% to 19% by weight based on the total weight of the uncured resin matrix. More preferably, the total amount of polyamide particles in the uncured resin ranges from 12% to 17% by weight based on the total weight of the uncured resin matrix.

[0069] The thermoplastic particle component may include a combination of polyimide particles and polyamide particles. A preferred polyimide particle is commercially available as P84 polyimide molding powder from HP Polymer GmbH, Lenzig, Austria. A suitable polyimide particle is also commercially available under the trade name P84NT from Evonik Industries, Austria. The polyimide used to make the particles is disclosed in U.S. Pat. No. 3,708,458, the contents of which are incorporated herein by reference. The polyimide is made by combining benzophenone-3,3',4,4'-tetracarboxylic dianhydride with a mixture of 4,4'-methylenebis(phenylisocyanate) and toluene diisocyanate (2,4- or 2,6-isomers). Amine analogs may be used in place of the aromatic isocyanates and diisocyanates. The CAS Registry Number for the polyimide is 58698-66-1.

[0070] Polyimide particles are made of the repeating monomer formula: [ka] wherein 10-90% of the R groups in the entire polymer are of the formula: [ka] and the remaining R groups in the polymer are [ka] It is.

[0071] The polyimide particles in the powder typically have a particle size in the range of 2 microns to 35 microns. A preferred polyimide powder contains particles with a particle size in the range of 2 to 30 microns, with an average particle size ranging from 5 microns to 15 microns. Preferably, at least 90% by weight of the polyimide particles in the powder are in the particle size range of 2 microns to 20 microns. The shape of the polyimide particles can be regular or irregular. For example, the particles can be substantially spherical or can be jagged particles.

[0072] The polyimide particles contain at least 95% polyimide by weight. Small amounts (up to 5% by weight) of other materials may be included in the particles as long as they do not adversely affect the overall properties of the particles. The glass transition temperature (Tg) of the polyimide particles should be about 330°C, and the density of the individual particles is 1.34 grams per cubic centimeter. The linear thermal expansion coefficient of the particles is 50.

[0073] The uncured resin matrix also includes a nanoparticle component. The nanoparticle component is composed of nanoscale solid inorganic particles. The nanoparticles may have a particle size on the order of 5-400 nanometers. An average particle size in the range of 10-200 nanometers is preferred. Exemplary nanoparticles include calcite nanoparticles, silica nanoparticles, barium sulfate nanoparticles, antimony pentoxide nanoparticles, and alumina silicate nanoparticles. The nanoparticles may be used alone or as a blend of nanoparticles. Calcite nanoparticles are preferred.

[0074] The amount of nanoparticles in the uncured resin matrix should be sufficient to increase both the compressive and tensile strength of the composite part made from the prepreg. It has been found that nanoparticle amounts less than 10 wt% based on the total weight of the uncured resin matrix result in an increase in tensile strength and a decrease in compressive strength of the composite part made from the prepreg. Higher nanoparticle loading levels, on the order of 15-25 wt% based on the total weight of the uncured resin matrix, have been found to increase both tensile and compressive strength. Thus, the amount of nanoparticles in the uncured resin matrix should be high enough to achieve an increase in both tensile and compressive strength.

[0075] To obtain the desired simultaneous increase in both tensile and compressive strength, the nanoparticle component should be present in the uncured resin matrix in an amount ranging from 10 to 30 weight percent based on the total weight of the uncured resin matrix. A preferred range is 12 to 30 weight percent based on the total weight of the uncured resin matrix. A range of 12 to 18 weight percent nanoparticles based on the total weight of the uncured resin matrix is ​​most preferred.

[0076] The nanoparticles may be added directly to the uncured resin matrix. However, it is preferred to disperse the nanoparticles in a suitable epoxy resin to form a nanoparticle / epoxy resin containing a concentrated dispersion of the nanoparticles. The particular epoxy resin in which the nanoparticles are dispersed to form the nanoparticle / epoxy resin can be any suitable epoxy resin, including bisphenol A epoxy resin, bisphenol F epoxy resin, trifunctional epoxy resin, and tetrafunctional epoxy resin. The amount of nanoparticles in the nanoparticle / epoxy resin can vary from 30 to 80% by weight and depends on the particular epoxy resin being used to form the nanoparticle / epoxy resin and the particular epoxy resin(s) used to form the resin component.

[0077] An exemplary procedure for making nanoparticles / epoxy resin is described in U.S. Patent No. 9,221,970, the contents of which are incorporated herein by reference. Nanoparticles are commercially available from several suppliers in the form of a dispersion of nanoparticles in one or more epoxy resins. For example, a dispersion of calcite nanoparticles in bisphenol A epoxy resin is available from 3M (St. Paul, Minnesota) under the trade name MATRIX RESIN 8830. MATRIX RESIN 8830 contains 57% by weight of calcite nanoparticles dispersed in bisphenol A epoxy resin.

[0078] The uncured resin matrix comprises at least one hardener. Suitable hardeners are those which promote the curing of the epoxy-functional compounds of the present invention, in particular those which promote the ring-opening polymerization of such epoxy compounds. In a particularly preferred embodiment, such hardeners include compounds which polymerize with the epoxy-functional compounds (single or multiple) in the ring-opening polymerization. Two or more of such hardeners may be used in combination.

[0079] Suitable hardeners include anhydrides, particularly polycarboxylic anhydrides, such as nadic anhydride (NA), methyl nadic anhydride (MNA-available from Aldrich), phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride (HHPA-Anhydrides and Chemicals Inc., Newark, NJ), methyl tetrahydrophthalic anhydride (MTHPA-Anhydrides and Chemicals Inc.), methyl hexahydrophthalic anhydride (MHHPA-Anhydrides and Chemicals Inc.), endomethylene tetrahydrophthalic anhydride, hexachloro endomethylene-tetrahydrophthalic anhydride (chlorendic anhydride-Velsicol Chemical). Examples of suitable polyanhydrides include but are not limited to: trimellitic anhydride, pyromellitic dianhydride, maleic anhydride (available from MA-Aldrich), succinic anhydride (SA), nonenylsuccinic anhydride, dodecenylsuccinic anhydride (available from DDSA-Anhydrides and Chemicals Inc.), polysebacic polyanhydride, and polyazelaic polyanhydride.

[0080] Further suitable curing agents are aromatic amines, such as 1,3-diaminobenzene, 1,4-diaminobenzene, 4,4'-diaminodiphenylmethane, and polyaminosulfones, such as 4,4'-diaminodiphenylsulfone (4,4'-DDS, available from Huntsman), 4-aminophenylsulfone, and 3,3'-diaminodiphenylsulfone (3,3'-DDS). Suitable curing agents may also include polyols such as ethylene glycol (available from EG-Aldrich), poly(propylene glycol), and poly(vinyl alcohol); and phenol-formaldehyde resins, such as phenol-formaldehyde resins having an average molecular weight of about 550-650, pt-butylphenol-formaldehyde resins having an average molecular weight of about 600-700, and pn-octylphenol-formaldehyde resins having an average molecular weight of about 1200-1400, available from Schenectady Chemicals Inc. (Schenectady, NY) as HRJ2210, HRJ-2255, and SP-1068, respectively. Additionally, for phenol-formaldehyde resins, a combination of CTU guanamine and a phenol-formaldehyde resin having a molecular weight of 398, available from Ajinomoto USA Inc. (Teaneck, NJ) as CG-125, is also suitable.

[0081] Various commercially available compositions may be used as the curing agent in the present invention. One such composition is AH-154, a dicyandiamide type formulation available from Ajinomoto USA Inc. Others that are suitable include Ancamide 400, a mixture of polyamide, diethyltriamine, and triethylenetetraamine, Ancamide 506, a mixture of amidoamine, imidazoline, and tetraethylenepentamine, and Ancamide 1284, a mixture of 4,4'-methylenedianiline and 1,3-benzenediamine, available from Pacific Anchor Chemical, Performance Chemical Division, Air Products and Chemicals, Inc., Allentown, Pennsylvania.

[0082] Additional suitable curing agents include imidazole (1,3-diaza-2,4-cyclopentadiene) available from Sigma Aldrich (St. Louis, Missouri), 2-ethyl-4-methylimidazole available from Sigma Aldrich, and boron trifluoride amine complexes such as Anchor 1170 available from Air Products & Chemicals, Inc.

[0083] Yet another suitable curing agent includes 3,9-bis(3-aminopropyl-2,4,8,10-tetroxaspiro[5.5]undecane, available commercially from Ajinomoto USA Inc. as ATU, as well as aliphatic dihydrazides also available from Ajinomoto USA Inc. as Ajicure UDH, and mercapto-terminated polysulfides available commercially from Morton International, Inc., Chicago, Ill., as LP540.

[0084] The curing agent(s) are selected to provide curing of the matrix at a suitable temperature. The amount of curing agent required to provide adequate curing of the matrix varies depending on many factors, including the type of resin being cured, the desired curing temperature and curing time. Curing agents typically include cyanoguanidines, aromatic and aliphatic amines, acid anhydrides, Lewis acids, substituted ureas, imidazoles and hydrazines. The specific amount of curing agent required for each particular situation can be determined by well-established routine experimentation.

[0085] Exemplary preferred curing agents include 4,4'-diaminodiphenyl sulfone (4,4'-DDS) and 3,3'-diaminodiphenyl sulfone (3,3'-DDS), both of which are commercially available from Huntsman Corporation (The Woodlands, Texas).

[0086] The hardener is present in an amount ranging from 10% to 30% by weight of the uncured resin matrix. In DEN / TRIF matrix resins, the hardener is present in an amount ranging from 10% to 30% by weight. More preferably, the hardener is present in an amount ranging from 15% to 25% by weight of the uncured resin matrix.

[0087] Accelerators may also be included to enhance or speed up the cure. Suitable accelerators are any uron compounds commonly used in the curing of epoxy resins. Specific examples of accelerators that may be used alone or in combination include N,N-dimethyl,N'-3,4-dichlorophenylurea (diuron), N'-3-chlorophenylurea (monuron), and preferably N,N-(4-methyl-m-phenylenebis[N',N'-dimethylurea] (e.g., Dyhard UR500 available from Degussa).

[0088] The uncured resin matrix of the present invention also includes a thermoplastic toughening agent. Any suitable thermoplastic polymer may be used as the toughening agent. Typically, the thermoplastic polymer is added to the resin mix as particles that dissolve in the resin mixture by heating, prior to the addition of the curing agent. Once the thermoplastic agent is substantially dissolved in the hot matrix resin precursor (i.e., the blend of epoxy resins), the precursor is cooled and the remaining ingredients (curing agent, nanoparticles / epoxy resin and insoluble thermoplastic particles) are added and mixed with the cooled resin blend.

[0089] Exemplary thermoplastic toughening agents / particles include any of the following thermoplastics, alone or in combination: polysulfones, polyethersulfones, polyetherimides, high performance hydrocarbon polymers, elastomers, and segmented elastomers.

[0090] A preferred toughening agent is, by way of example, a particulate polyethersulfone (PES) sold under the trade name Sumikaexcel 5003P and available from Sumitomo Chemicals (New York, NY). Alternatives to 5003P are non-hydroxyl terminated grades such as Solvay polyethersulfone 105RP or Solvay 1054P, available from Solvay Chemicals (Houston, TX). Densified PES particles may be used as the toughening agent. The form of the PES is not particularly important since the PES dissolves during the formation of the resin. Densified PES particles may be made according to the teachings of U.S. Pat. No. 4,945,154, the contents of which are incorporated herein by reference. Densified PES particles are also available under the trade name HRI-1 from Hexcel Corporation (Dublin, CA). The average particle size of the toughening agent should be less than 100 microns to promote and ensure complete dissolution of the PES in the matrix.

[0091] In DEN / TRIF matrix resins, the toughening agent is present in the range of 5% to 15% by weight based on the total weight of the uncured resin matrix. Preferably, the toughening agent is present in the range of 7% to 12% by weight. More preferably, the toughening agent is present in the range of 8% to 11% by weight.

[0092] The matrix resin may also contain additional components such as performance enhancers or modifiers, so long as they do not adversely affect the adhesion and life of the prepreg or the strength and damage tolerance of the cured composite part. The performance enhancers or modifiers may be selected from, for example, core-shell rubbers, flame retardants, wetting agents, pigments / dyes, UV absorbers, anti-fungal compounds, fillers, conductive particles, and viscosity modifiers.

[0093] Exemplary core-shell rubber (CSR) particles are composed of a crosslinked rubber core, typically a copolymer of butadiene, and a shell composed of styrene, methyl methacrylate, glycidyl methacrylate, and / or acrylonitrile. The core-shell particles are usually provided as particles dispersed in an epoxy resin. The particle size range is typically 50-150 nm. Suitable CSR particles are described in detail in U.S. Patent Application Publication No. 2007 / 0027233A1, the contents of which are incorporated herein by reference. A preferred core-shell particle is MX core-shell particle available from Kane Ace (Pasadena, Texas). A preferred core-shell particle for inclusion in DEN / TRIF matrix resin is Kane Ace MX-418. MX-418 is supplied as a 25% by weight suspension of core-shell particles in a tetrafunctional epoxy resin. The core-shell particles in MX-418 are polybutadiene (PBd) core-shell particles with an average particle size of 100 nanometers.

[0094] Suitable conductive particles include, by way of example only, any of the following: silver, gold, copper, aluminum, nickel, conductive grade carbon, buckminsterfullerene, carbon nanotubes, and carbon nanofibers, either alone or in combination. Metal-coated fillers, such as nickel-coated carbon particles and silver-coated copper particles, may also be used.

[0095] Potato-shaped graphite (PSG) particles are suitable conductive particles. The use of PSG particles in carbon fiber / epoxy resin composites is described in detail in U.S. Patent Application Publication No. 2015 / 0179298A1, the contents of which are incorporated herein by reference. PSG particles are commercially available from NGS Naturgraphit (Germany) as SG25 / 99.95 SC particles, or from Japan Power Graphite Co., Ltd. (Japan) as GHDR-15-4 particles. These commercially available PSG particles have an average particle size of 10-30 microns, and the GHDR-15-4 particles have a vapor-deposited coating of carbon on the outer surface of the PSG particles.

[0096] The uncured resin matrix may contain a small amount (less than 5% by weight, preferably less than 1% by weight) of additional epoxy or non-epoxy thermosetting polymer resin. In the case of DEN / TRIF / TETF matrix resin, the epoxy resin component contains at least 95% by weight of DEN, TRIF and TETF, more preferably at least 99% by weight of three epoxy resins. In the case of DEN / TRIF matrix resin, the epoxy resin component contains at least 95% by weight of DEN and TRIF, more preferably at least 99% by weight of two epoxy resins. Suitable additional epoxy resins include difunctional epoxy resins, such as bisphenol A and bisphenol F type epoxy resins. Suitable non-epoxy thermosetting resin materials for the present invention include, but are not limited to, phenol formaldehyde, urea-formaldehyde, 1,3,5-triazine-2,4,6-triamine (melamine), bismaleimide, vinyl ester resin, benzoxazine resin, phenolic resin, polyester, cyanate ester resin or any combination thereof. The additional thermosetting resin, when present, is preferably selected from epoxy resins, cyanate ester resins, benzoxazine and phenolic resins.

[0097] The uncured resin matrix is ​​made according to standard prepreg matrix resin processing. Generally, when two or more epoxy resins are used in the resin component, the epoxy resins are mixed together at room temperature to form a resin mix to which the thermoplastic toughening agent is added. The mixture is then heated to about 120°C for about 1-2 hours to dissolve the thermoplastic toughening agent. The mixture is then cooled to about 80°C and the remaining components (thermoplastic particle component, nanoparticles / epoxy resin, hardener, and other additives, if present) are mixed into the resin to form the final uncured resin matrix that is impregnated into the fiber reinforcement.

[0098] The uncured resin is applied to the fiber reinforcement to form an uncured resin matrix according to any of the known prepreg manufacturing techniques. The fiber reinforcement may be fully or partially impregnated by the uncured resin. In an alternative embodiment, the uncured resin may be applied to the fiber reinforcement as a separate layer that is in close proximity to and in contact with the fiber reinforcement but does not substantially impregnate the fiber reinforcement. Prepregs, also called semipregs, are usually covered on both sides with a protective film to avoid premature curing, and are usually rolled up for storage and transportation at temperatures maintained well below room temperature. The actual resin matrix is ​​not formed until further processing of the semipreg. Any of the other prepreg manufacturing processes and storage / shipping systems may be used if desired.

[0099] The fiber reinforcement of the prepreg may be selected from any glass fiber, carbon or aramid (aromatic polyamide) fiber. The fiber reinforcement is preferably carbon fiber. The preferred carbon fiber is in the form of a tow containing 3,000 to 50,000 carbon filaments (3K to 50K). Commercially available carbon fiber tows containing 6,000 or 24,000 carbon filaments (6K or 24K) are preferred.

[0100] The uncured matrix resin of the present invention has a carbon tow containing 6,000 to 24,000 filaments, a tensile strength of 750 to 860 Ksi, a tensile modulus of 35 to 45 Msi, a failure strain of 1.5 to 2.5%, and a density of 1.6 to 2.0 g / cm.3 and is particularly effective in providing a laminate with high strength properties and damage tolerance when the weight per length is between 0.2 and 0.6 g / m. IM7 carbon tows (available from Hexcel Corporation) in 6K and 12K are preferred. IM7 12K fibers have a tensile strength of 820 Ksi, a tensile modulus of 40 Msi, a strain to failure of 1.9% and a density of 1.78 g / cm. 3 and the weight per length is 0.45 g / m. IM7 6K fiber has a tensile strength of 800 Ksi, a tensile modulus of 40 Msi, a strain at break of 1.9%, and a density of 1.78 g / cm. 3 and has a weight per length of 0.22 g / m. IM7 fiber and carbon fibers having similar properties are generally considered to be intermediate modulus carbon fibers. IM8 carbon fiber, available from Hexcel Corporation (Dublin, Calif.), is also a preferred type of intermediate modulus carbon fiber.

[0101] The fiber reinforcement may include cracked (i.e. stretch-broken) or selectively discontinuous fibers, or continuous fibers. The use of cracked or selectively discontinuous fibers may facilitate the lay-up of the composite before it is fully cured and improve its shaping ability. The fiber reinforcement may be in the form of a woven, non-crimped, non-woven, unidirectional or multiaxial woven structure, such as, for example, quasi-isotropic chopped prepregs used to form sheet molding compounds. The woven forms may be selected from plain, satin, or twill styles. The non-crimped and multiaxial forms may have several layers and fiber orientations. Such styles and forms are well known in the composite reinforcement art and are commercially available from several companies, including Hexcel Reinforcements (Les Avenieres, France).

[0102] The prepreg may be in the form of a continuous tape, towpreg, web, or chopped length (chopping and slitting operations may be performed at any time after impregnation). The prepreg may be an adhesive or surfacing film and may have embedded carriers of various forms, both woven, knitted, and nonwoven. The prepreg may be fully or only partially impregnated, for example to facilitate air removal during curing.

[0103] The following exemplary DEN / TRIF resin formulations may be impregnated into a fiber substrate to form a resin matrix according to the present invention (all weight percentages are based on the total weight of the uncured resin matrix): 32% to 36% by weight of triglycidyl-m-aminophenol (MY0600); 6% to 10% by weight of a hydrocarbon novolac epoxy resin (TACTIX 556 or XD-1000-2L); 7% to 11% by weight of polyethersulfone (5003P) as a toughening agent; 2% to 7% by weight of crosslinked polyamide 12 particles (ORGASOL CG352); 9% to 13% by weight of non-crosslinked polyamide 11 particles (Rislan PA11) (the weight ratio of non-crosslinked polyamide particles to crosslinked polyamide 12 particles is 2.5:1.0 to 3.0:1, preferably 2.7:1 to 2.8:1); 13% to 17% by weight of calcite nanoparticles; and 16% to 21% by weight of 4,4'-DDS or 3,3'-DDS as a curing agent.

[0104] Another exemplary DEN / TRIF matrix resin includes 32% to 36% by weight triglycidyl-m-aminophenol (MY0600); 7% to 11% by weight polyethersulfone (5003P) as a toughening agent; 9% to 13% by weight polyamide 11 particles (Rislan PA11); 2% to 7% by weight hybrid polyamide particles (the weight ratio of polyamide 11 particles to hybrid polyamide particles is 2.5:1.0 to 3.0:1, preferably 2.7:1 to 2.8:1); 13% to 17% by weight calcite nanoparticles; and 16% to 21% by weight 4,4'-DDS or 3,3'-DDS as a curing agent.

[0105] Another exemplary matrix resin includes 18% to 22% by weight of tetrafunctional epoxy resin (MY721); 43% to 47% by weight of matrix resin 8830; 5% to 9% by weight of polyethersulfone (5003P) as a toughening agent; 11% to 15% by weight of polyamide 11 particles (Rislan PA11); and 13% to 17% by weight of 4,4'-DDS or 3,3'-DDS as a curing agent.

[0106] The prepregs can be molded using any of the standard techniques used to form composite parts. Typically, one or more layers of the prepregs are placed in a suitable mold and cured to form the final composite part. The prepregs of the present invention can be fully or partially cured using any suitable temperature, pressure, and time conditions known in the art. Typically, the prepregs will be cured in an autoclave at a temperature of 160°C to 190°C. The composites can be cured using a method selected from microwave radiation, electron beam, gamma radiation, or other suitable thermal or non-thermal radiation.

[0107] Composite parts made from the improved prepregs of the present invention find use in the construction of articles such as primary and secondary aerospace structures (such as wings, fuselages and bulkheads), but are also useful in many other high performance composite applications including automotive, rail and marine applications where high compressive strength, interlaminar fracture toughness and impact damage resistance are required.

[0108] An example of implementation is as follows.

[0109] Example 1 A preferred exemplary resin formulation according to the present invention is shown in Table 1. The matrix resin was prepared by mixing the epoxy components (hydrocarbon epoxy novolac resin and trifunctional metaglycidylamine) with polyethersulfone at room temperature to form a resin blend, which was then heated to 120° C. for 60 minutes to completely dissolve the polyethersulfone. The mixture was cooled to 80° C. and the remaining ingredients, including calcite nanoparticles, were added and mixed thoroughly. The calcite nanoparticles were added in the form of nanoparticle / epoxy resin containing 60% by weight of calcite nanoparticles dispersed in MY0610 resin. The calcite nanoparticles had a particle size in the range of about 100-200 nanometers.

[0110] The hybrid polyamide particles used in this example are described according to the weight percent of amorphous (Trogamid® CX9704) and semi-crystalline (Trogamid® CX9705) polyamide present in each particle. As noted above, the hybrid polyamide particles containing a mixture of 70% by weight CX9704 polyamide and 30% by weight CX9705 polyamide are identified as hybrid particles "(70A / 30SC)" and the hybrid polyamide particles containing a mixture of 30% by weight CX9704 polyamide and 70% by weight CX9705 polyamide are identified as hybrid polyamide particles "(30A / 70SC)." The hybrid polyamide particles used in this example ranged in size from 3 microns to 10 microns with an average particle size of 6 microns. [Table 2]

[0111] Exemplary prepregs were prepared by impregnating one or more layers of unidirectional 12K carbon fiber with the resin formulations in Table 1. Unidirectional carbon fiber was used to make prepregs with matrix resin at 35 weight percent of the total uncured prepreg weight and fiber areal weight of 192 grams per square meter (gsm). Standard prepreg manufacturing procedures were used to prepare 8-ply and 16-ply laminates. Laminates were cured in an autoclave at 177°C for approximately 2 hours. The cured 8-ply laminates were tested to determine tensile strength (open-hole tensile) and the cured 16-ply laminates were tested to determine compressive strength (open-hole compressive).

[0112] Open hole tensile (OHT) and open hole compression (OHC) are standard tests performed according to Boeing test method BSS 7260 per BMS 8-276. OHT was measured at room temperature on an 8-ply laminate in which the unidirectional carbon fiber plies were oriented 25 / 50 / 25 relative to each other. OHC was measured at room temperature on a 16-ply laminate in which the unidirectional carbon fiber plies were also oriented 25 / 50 / 25 relative to each other. The OHT was 75.2 ksi (kilograms per square inch) and the OHC was 49.5 ksi.

[0113] Example 2 An exemplary prepreg with a resin matrix having the formulation shown in Table 2 was prepared similarly to Example 1. [Table 3]

[0114] An 8-ply and a 16-ply laminate were prepared as in Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 75.6 ksi and the OHC was 50.2 ksi.

[0115] A comparative example was run similarly to Example 2, except the amount of calcite nanoparticles was reduced to 9.0 wt% and the amounts of MY0610 resin and 4,4'-DDS were increased by 3.8 wt% and 2.2 wt%, respectively. 8-ply and 16-ply laminates were prepared similar to Example 1, cured at room temperature, and tested for OHC and OHT. The OHT was 75.4 ksi and the OHC was 45.6 ksi.

[0116] A second comparative example was run similarly to Example 2, except the amount of calcite nanoparticles was reduced to 0 wt%, and the amounts of XD-1000-2L, MY0610 resin, and 4,4'-DDS were increased by 10.0 wt%, 1.6 wt%, and 3.4 wt%, respectively. 8-ply and 16-ply laminates were prepared similarly to Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 73.5 ksi and the OHC was 47.8 ksi.

[0117] Table A shows a comparison of the results of Examples 1-2 and the comparative test. [Table 4]

[0118] As can be seen from Table A, when only 9 wt% calcite nanoparticles were included in the matrix resin, OHT increased and OHC decreased. However, when 15 wt% calcite nanoparticles were included in the matrix resin, both OHT and OHC increased (Examples 1 and 2). Increasing the amount of calcite nanoparticles from 9 wt% to 15 wt% was also expected to decrease OHC. Therefore, the increase in both OHT and OHC observed at 15 wt% calcite nanoparticle loading was unexpected.

[0119] Based on the above findings, the amount of nanoparticles contained in the matrix resin is preferably sufficient to increase both OHT and OHC. The amount of nanoparticles contained in the matrix resin is preferably 10% to 30% by weight based on the total weight of the resin matrix. A more preferred range is 12% to 25% by weight of nanoparticles based on the total weight of the resin matrix.

[0120] Exemplary resin samples having the formulations shown in Table 2 were prepared and cured at 177°C for 2 hours to form exemplary cured neat resin samples (no fiber support) which were tested at room temperature according to standard test procedures to determine flexural strength and flexural modulus. The cured neat resin sample had a flexural strength of 20.2 ksi and a flexural modulus of 673.0 ksi.

[0121] Comparative resin samples were prepared that were identical to the formulations listed in Table 2, except that the amount of calcite nanoparticles was reduced to 0 wt.% and the amounts of XD-1000-2L, MY0610 resin, and 4,4'-DDS were increased by 10.0 wt.%, 1.6 wt.%, and 3.4 wt.%, respectively. As with the exemplary pure resin samples, the comparative pure resin samples were cured at room temperature and tested for flexural strength and flexural modulus. The cured comparative pure resin sample had a flexural strength of 22.9 ksi and a flexural modulus of 572.0 ksi.

[0122] Comparison of the test results of the exemplary cured neat resin and the comparative cured neat resin shows that when 15 wt% calcite nanoparticles were included in the resin, the flexural strength decreased and the flexural modulus increased. This result was as expected. This further illustrates the unexpected nature of the increase observed in both OHC and OHT when the resin was used as a resin matrix for a fibrous laminate when 15 wt% calcite nanoparticles were included in the resin.

[0123] Example 3 An exemplary prepreg with a resin matrix having the formulation shown in Table 3 was prepared similarly to Example 1. [Table 5]

[0124] An 8-ply and a 16-ply laminate were prepared as in Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 74.6 ksi and the OHC was 50.0 ksi.

[0125] A comparative example was run similarly to Example 3, except the amount of calcite nanoparticles was reduced to 0 wt% and the amounts of XD-1000-2L, MY0610 resin, and 3,3-DDS were increased by 10.0 wt%, 1.6 wt%, and 3.4 wt%, respectively. 8-ply and 16-ply laminates were prepared similarly to Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 68.7 ksi and the OHC was 45.4 ksi.

[0126] The resin matrix containing 15 wt % calcite nanoparticles (Example 3) had an OHT that was 8.4% higher than the control, and an OHC that was 9.7% higher than the control.

[0127] Example 4 An exemplary prepreg with a resin matrix having the formulation shown in Table 4 was prepared similarly to Example 1. Calcite nanoparticles were added to the resin mixture in the form of MATRIX RESIN 8830, which contains 57% by weight of calcite nanoparticles dispersed in bisphenol A resin. The calcite nanoparticles had a particle size in the range of approximately 100-200 nanometers. [Table 6]

[0128] An 8-ply and a 16-ply laminate were prepared as in Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 78.5 ksi and the OHC was 48.6 ksi.

[0129] A comparative example was run similarly to Example 4, except the amount of calcite nanoparticles was reduced to 0 wt% and the amounts of MY0721 resin, DER 332 resin, and 4,4'-DDS were increased by 8.7 wt%, 8.7 wt%, and 8.2 wt%, respectively. 8-ply and 16-ply laminates were prepared similarly to Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 66.1 ksi and the OHC was 40.9 ksi.

[0130] The resin matrix containing 25.6 wt% calcite nanoparticles (Example 4) had both 19% higher OHT and OHC than the control, which was unexpected considering the previous comparative example where the addition of less than 10 wt% calcite nanoparticles increased OHT and decreased OHC.

[0131] Example 5 An exemplary prepreg with a resin matrix having the formulation shown in Table 5 was prepared similar to Example 1. Calcite nanoparticles were added to the resin mixture in the form of MATRIX RESIN 8830, which contains 57 wt. % calcite nanoparticles dispersed in bisphenol A resin. [Table 7]

[0132] An 8-ply and a 16-ply laminate were prepared as in Example 1, cured at room temperature, and tested for OHT and OHC. The OHT was 70.9 ksi and the OHC was 46.9 ksi.

[0133] Having thus described exemplary embodiments of the present invention, those skilled in the art should note that the scope of the disclosure is merely exemplary, and that various other changes, modifications, and alterations may be made within the scope of the present invention. Accordingly, the present invention is not limited to the above-described embodiments, but only by the appended claims. Various aspects or embodiments that can be included in the present invention are summarized as follows. [1]. A prepreg, A) Reinforcing fibers, and B) an uncured resin matrix, a) a resin component comprising one or more epoxy resins; b) a thermoplastic particle component comprising thermoplastic particles, the thermoplastic particle component being present in an amount ranging from 10 to 20% by weight based on the total weight of the uncured resin matrix; c) a thermoplastic toughening agent comprising polyethersulfone, the thermoplastic toughening agent being present in an amount ranging from 5 to 15 weight percent based on the total weight of the uncured resin matrix; d) a nanoparticle component comprising nanoparticles, the nanoparticle component being present in an amount ranging from 10 to 30% by weight based on the total weight of the uncured resin matrix; and e) Hardener An uncured resin matrix comprising A prepreg comprising: [2]. 2. The prepreg of claim 1, wherein the nanoparticles include calcite nanoparticles. [3]. The prepreg according to item 1, wherein the thermoplastic particles include polyamide particles. [4]. The prepreg according to item 2, wherein the polyamide particles include non-crosslinked polyamide particles and crosslinked polyamide particles. [5]. 5. The prepreg according to claim 4, wherein the non-crosslinked particles comprise polyamide 11. [6]. 6. The prepreg according to item 5, wherein the crosslinked polyamide particles comprise crosslinked polyamide 12. [7]. The polyamide particles comprise hybrid polyamide particles, each of the hybrid polyamide particles comprises a mixture of a semi-crystalline polyamide and an amorphous polyamide, the amorphous polyamide is present in an amount of 20 to 80% by weight based on the total weight of the hybrid polyamide particles, the semi-crystalline polyamide is present in an amount of 20 to 80% by weight based on the total weight of the hybrid polyamide particles, and the semi-crystalline polyamide and the amorphous polyamide are reacted with 1,10-decanedicarboxylic acid and a compound of the formula [C1] JPEG0007637677000016.jpg53100 4. The prepreg according to claim 3, comprising different stereoisomeric forms of the polyamide, which are polymer condensation products with an amine component having the formula: [8]. The prepreg according to item 1, wherein the curing agent is an aromatic amine selected from the group consisting of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone. [9]. A composite part or structure formed by curing a composite material containing the prepreg according to item 1 above.

[10] . 10. The composite part or structure according to claim 9, wherein the composite part or structure forms at least a part of a primary structure of an aircraft.

[11] . 1. A method of making a prepreg that can be cured to form a composite part, comprising: A) providing reinforcing fibers comprising carbon fibers; and B) impregnating the reinforcing fibers with an uncured resin matrix, the uncured resin matrix being a) a resin component comprising one or more epoxy resins; b) a thermoplastic particle component comprising thermoplastic particles, the thermoplastic particle component being present in an amount ranging from 10 to 20% by weight based on the total weight of the uncured resin matrix; c) a thermoplastic toughening agent comprising polyethersulfone, the thermoplastic toughening agent being present in an amount ranging from 5 to 15 weight percent based on the total weight of the uncured resin matrix; d) a nanoparticle component comprising nanoparticles, the nanoparticle component being present in an amount ranging from 12 to 30% by weight based on the total weight of the uncured resin matrix; and e) Hardener Including steps A method for making a prepreg comprising:

[12] . 12. The method of making a prepreg according to claim 11, wherein the nanoparticles comprise calcite nanoparticles.

[13] . 12. The method for making a prepreg according to claim 11, wherein the thermoplastic particles comprise polyamide particles.

[14] . 13. The method for producing a prepreg according to item 12 above, wherein the polyamide particles include non-crosslinked polyamide particles and crosslinked polyamide particles.

[15] . 15. The method for making a prepreg according to claim 14, wherein the non-crosslinked particles comprise polyamide 11.

[16] . 16. The method for making a prepreg according to item 15 above, wherein the crosslinked polyamide particles comprise crosslinked polyamide 12.

[17] . The polyamide particles comprise hybrid polyamide particles, each of the hybrid polyamide particles comprises a mixture of a semi-crystalline polyamide and an amorphous polyamide, the amorphous polyamide is present in an amount of 20 to 80% by weight based on the total weight of the hybrid polyamide particles, the semi-crystalline polyamide is present in an amount of 20 to 80% by weight based on the total weight of the hybrid polyamide particles, and the semi-crystalline polyamide and the amorphous polyamide are reacted with 1,10-decanedicarboxylic acid and a compound of the formula [Case 2] JPEG0007637677000017.jpg53100 14. A method for making a prepreg according to claim 13, comprising the step of:

[18] . 12. The method for producing a prepreg according to item 11, wherein the curing agent is an aromatic amine selected from the group consisting of 3,3'-diaminodiphenylsulfone and 4,4'-diaminodiphenylsulfone.

[19] . A method for making a composite part or a composite structure, comprising the steps of providing a composite material comprising the prepreg described in item 1 above, and curing the composite material to form the composite part or the composite structure.

[20] . 20. A method for making a composite part or structure according to claim 19, wherein the composite part or structure forms at least a part of a primary structure of an aircraft.

Claims

1. A prepreg, A) reinforcing fibers, and B) an uncured resin matrix, a) a resin component comprising one or more epoxy resins; b) a thermoplastic particle component comprising thermoplastic particles, the thermoplastic particle component being present in an amount ranging from 10 to 20 weight percent based on the total weight of the uncured resin matrix; c) a thermoplastic toughening agent comprising polyethersulfone, the thermoplastic toughening agent being present in an amount ranging from 5 to 15 weight percent based on the total weight of the uncured resin matrix; d) a nanoparticle component comprising nanoparticles, the nanoparticle component being present in an amount ranging from 10 to 30 wt % based on the total weight of the uncured resin matrix; and e) Hardener An uncured resin matrix comprising Including, the thermoplastic particles include polyamide particles; The polyamide particles comprise hybrid polyamide particles, each of the hybrid polyamide particles comprises a mixture of a semi-crystalline polyamide and an amorphous polyamide, the amorphous polyamide is present in an amount of 20 to 80 wt % based on the total weight of the hybrid polyamide particles, the semi-crystalline polyamide is present in an amount of 20 to 80 wt % based on the total weight of the hybrid polyamide particles, and the semi-crystalline polyamide and the amorphous polyamide are reacted with 1,10-decanedicarboxylic acid and a compound of formula (AC-G): 【Chemistry 1】 wherein R 2 is hydrogen and R 1 is either methyl or hydrogen; Prepreg.

2. The prepreg of claim 1 , wherein the nanoparticles comprise calcite nanoparticles.

3. 2. The prepreg of claim 1, wherein the polyamide particles comprise non-crosslinked polyamide particles and crosslinked polyamide particles.

4. 4. The prepreg of claim 3, wherein the non-crosslinked polyamide particles comprise polyamide 11.

5. 5. The prepreg of claim 4, wherein the crosslinked polyamide particles comprise crosslinked polyamide 12.

6. The semicrystalline polyamide and the amorphous polyamide are formed by reacting 1,10-decanedicarboxylic acid with a compound of the formula 【Chemistry 2】 2. The prepreg of claim 1, comprising different stereoisomeric forms of the polyamide which are polymeric condensation products with an amine component having the formula:

7. 2. The prepreg of claim 1, wherein the curing agent is an aromatic amine selected from the group consisting of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone.

8. 13. A composite part or structure formed by curing a composite material comprising the prepreg of claim 1.

9. The composite part or structure of claim 8 , wherein the composite part or structure forms at least a portion of a primary structure of an aircraft.

10. 1. A method of making a prepreg that can be cured to form a composite part, comprising: A) providing reinforcing fibers comprising carbon fibers; and B) impregnating the reinforcing fibers with an uncured resin matrix, the uncured resin matrix being: a) a resin component comprising one or more epoxy resins; b) a thermoplastic particle component comprising thermoplastic particles, the thermoplastic particle component being present in an amount ranging from 10 to 20 weight percent based on the total weight of the uncured resin matrix; c) a thermoplastic toughening agent comprising polyethersulfone, the thermoplastic toughening agent being present in an amount ranging from 5 to 15 weight percent based on the total weight of the uncured resin matrix; d) a nanoparticle component comprising nanoparticles, the nanoparticle component being present in an amount ranging from 12 to 30 wt % based on the total weight of the uncured resin matrix; and e) Hardener Including steps Including, the thermoplastic particles include polyamide particles; The polyamide particles comprise hybrid polyamide particles, each of the hybrid polyamide particles comprises a mixture of a semi-crystalline polyamide and an amorphous polyamide, the amorphous polyamide is present in an amount of 20 to 80 wt % based on the total weight of the hybrid polyamide particles, the semi-crystalline polyamide is present in an amount of 20 to 80 wt % based on the total weight of the hybrid polyamide particles, and the semi-crystalline polyamide and the amorphous polyamide are reacted with 1,10-decanedicarboxylic acid and a compound of formula (AC-G): 【Chemistry 3】 wherein R 2 is hydrogen and R 1 is either methyl or hydrogen; A method for making a prepreg.

11. The method of making a prepreg according to claim 10, wherein the nanoparticles comprise calcite nanoparticles.

12. 11. The method of making a prepreg according to claim 10, wherein the polyamide particles comprise non-crosslinked and crosslinked polyamide particles.

13. 13. The method of making a prepreg according to claim 12, wherein the non-crosslinked polyamide particles comprise polyamide 11.

14. 14. The method of making a prepreg according to claim 13, wherein the crosslinked polyamide particles comprise crosslinked polyamide 12.

15. The semicrystalline polyamide and the amorphous polyamide are formed from 1,10-decanedicarboxylic acid and a compound represented by the formula: 【Chemistry 4】 11. The method of making the prepreg of claim 10, comprising different stereoisomeric forms of the polyamide which are polymeric condensation products with an amine component having the formula:

16. The method of making a prepreg according to claim 10, wherein the curing agent is an aromatic amine selected from the group consisting of 3,3'-diaminodiphenylsulfone and 4,4'-diaminodiphenylsulfone.

17. 13. A method of making a composite part or structure comprising the steps of providing a composite material comprising the prepreg of claim 1 and curing the composite material to form the composite part or structure.

18. 20. The method of making a composite part or structure according to claim 17, wherein the composite part or structure forms at least a portion of a primary structure of an aircraft.

Citation Information

Patent Citations

  • Nanocalcite composite materials

    JP2012512950A

  • Fiber-reinforced polymer composites with hard interphase

    JP2016503102A

  • Composite material with thermoplastic toughened novolac-based epoxy resin matrix

    US20170369663A1